Differences in General Education in Vocational and High Schools: Characteristics of Teachers and Teaching Practices in Mathematics - Yulia Koreshnikova; Andrey Zakharov; Fedor Dudyrev (Вопросы образования, 2018)
More and more middle school graduates opt for vocational schools every year. They are normally less academically successful students from lower economicand cultural backgrounds. Still, the vocational education system must provide the chance to have a quality general education to anyone who follows this trajectory after the ninth grade. The article uses findings of the Trajectories in Education and Careers longitudinal study to compare the important conditions of obtaining a general mathematical education, i. e. the professional and demographic characteristics of vocational and high school teachers and their teaching practices. The comparison reveals an inequality in students’ access to educational resources depending on the chosen trajectory.The differences revealed are related to the institutional characteristics of the two trajectories and make it possible to say that the latter embrace different types of general education.